The Positions of the Slovak Public and Political Elites Regarding Foreign Policy and European Integration (Czech Journal of International Relations, 1999)
In Czechoslovakia, after 1989 there was no clarity on the foreign political orientation of the state. This was also the result of the existence of Jive or six concepts that had arisen in connection with Central Europe in Europe, in the US and the USSR.In the end, the concept of the selective admission of certain designated post-socialist countries to NATO and the EU triumphed in Western Europe. When analysing foreign political considerations in Slovakia one cannot overlook the earlier experiences of the Slovak population. The Slovaks had been compelled for years to adopt a defensive attitude towards assimilation trends by foreign nations. The attitude towards the Hungarians appears to be of key significance as this was the primary foreign element against which the Slovaks had to stand up. This is the reason for continuing isolationist trends in Slovakia. At the same time, they have no tradition of their own statehood. The Slovaks were involved in the foreign policy of states to which the Slovaks belonged, certain Slovaks were even Ministers of Foreign Affairs, but Slovak politicians never carried responsibilities on their own, without politicians from the partner states as part of a common state.The policy vis-à-vis the other nations of the Habsburg monarchy – Hungary and Czechoslovakia – was regarded as the primary “international policy”. Slovakia had a positive image neither in the US nor in Western Europe, it was merely in the shadow of its neighbours. But the decisive factors of the integration fiasco in 1997 were the personal attitudes of the then Prime Minister as well as of his colleagues, and the concentration of the ruling elite on the distribution of property as part of the privatization process. Outright opponents of integration in the EU and NATO include only the political underground and, to some extent, also the Slovak National Party, SNS. The other parliamentary parties support integration in their programmes. But in the case of HZDS, interest in integration only went to the limit where acceptance of the rules applying in the EU did not endanger the division of the privatization cake. The Democratic Party is an enthusiastic supporter of integration. In this party, it is a question of ideological support. This party at times finds itself in a position where it is unofficially accused of paying more attention to “Western” interests than to Slovak interests.In backing membership in the EU and NATO, the Party of the Democratic Left and the Party of Civic Understanding proceed from an analysis of the situation and explain it by rational arguments on benefits for Slovakia. The Hungarian Coalition Party sees in integration in the EU a certain form of unification with the Hungarians and Hungary, in Romania and elsewhere.